A cyclic peptide-based anti-pollution electrochemical sensor and its preparation method and application
By modifying the surface of the electrochemical sensor with cyclic peptide-based zwitterionic peptides to form an anti-fouling layer, the biological pollution problem of electrochemical sensors during long-term use in the marine environment is solved, and higher anti-fouling performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411625462.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Existing electrochemical sensors are susceptible to biological pollution in seawater when used in marine environments for a long time, resulting in reduced sensitivity and shortened service life.
The surface modification is carried out using cyclic peptide-based zwitterionic peptides to form an anti-fouling layer to improve the anti-fouling performance of the electrochemical sensor. Specific methods include depositing an rGO-PEDOT layer on a glassy carbon electrode, preparing a calcium ion selective membrane, and incubating an autonomously designed polypeptide solution on its surface to form a stable annular structure and hydrated layer.
It significantly reduces the adhesion of bacterial cells and the formation of biofilms, extends the service life of the sensor, maintains good selectivity and stability, and ensures the stable and reliable detection of calcium ions in seawater.
Smart Images

Figure CN119198851B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of marine chemistry, and relates to an anti-pollution type electrochemical sensor based on cyclic peptides, a preparation method and an application thereof. Specifically, an environmentally friendly all-solid-state calcium ion selective electrochemical sensor with anti-pollution ability is disclosed for monitoring calcium ions in the ocean. Background Art
[0002] All-solid-state ion selective electrodes (ISEs) have become the main tools for real-time in-situ quantitative detection of ions due to their advantages such as convenient operation, portability, and low cost. In recent years, ISEs have become an effective means for evaluating ocean changes. However, there are still some drawbacks for long-term ocean detection. Since ion selective electrodes are easily affected by bacteria or proteins in seawater, the sensitivity of the sensor is reduced and the service life is shortened. Marine biofouling on the surface is a dynamic development process. When the electrode surface contacts seawater, polysaccharides and proteins can adsorb onto the electrode surface within a few seconds. When suspended bacteria approach the cell membrane, they can adsorb onto the electrode surface within a few hours through electrostatic and hydrophobic interactions, and a dense biofilm is formed after several days, and large marine invertebrates appear after several weeks. Therefore, developing polymer membranes with anti-pollution properties is a basic strategy to solve marine biofouling.
[0003] Developing anti-pollution coatings is considered an effective strategy to protect polymer sensing membranes from biofouling. By coating bactericidal materials such as silver nanomaterials, antimicrobial peptides, or antibacterial agents on the surface of the polymer sensing membrane, it is used to kill microorganisms on the surface of the polymer sensing membrane to prevent the formation of biofilms. However, coating bactericidal materials on the surface of the polymer sensing membrane cannot completely inhibit the non-specific adhesion of microorganisms, and there are still some bacteria that adhere to the surface of the polymer sensing membrane after death, ultimately leading to fouling on the surface of the polymer sensing membrane and affecting the detection performance of the sensor. Therefore, another strategy is to use hydrophilic materials such as polyethylene glycol, zwitterionic polymers, etc. to form a hydrated layer on the electrode surface to resist biofouling. Although hydrophilic materials exhibit excellent anti-pollution functions, there are still problems such as being easily degraded by enzymes, being easily oxidized in the biological environment, and the preparation process being cumbersome.
[0004] Polypeptides have received extensive attention as a non-toxic and environmentally friendly anti-fouling coating material. Due to its advantages such as easy synthesis and modification, and adjustable structure, it has been commonly used in recent years to construct anti-fouling coatings on the surface of sensors. The present invention uses hydrophilic zwitterionic peptides to modify the electrode surface, thus solving the problem of marine biofouling faced by electrochemical sensors when applied in seawater for a long time. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide an anti-pollution type electrochemical sensor based on cyclic peptides, which is an electrochemical sensor for detecting calcium ions in seawater prepared by surface modification of zwitterionic peptides, so as to improve the environmental compatibility of marine sensors and achieve stable and reliable detection of calcium ions in seawater while preventing bacterial pollution.
[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0007] The first technical object of the present invention is to provide an anti-pollution type electrochemical sensor based on cyclic peptides. The electrochemical sensor uses a glassy carbon electrode as the substrate, reduced graphene oxide and 3,4-ethylenedioxythiophene as the solid conduction layer, a calcium ion selective membrane as the detection layer, and a self-designed polypeptide as the anti-fouling layer, namely the GC / rGO-PEDOT / Ca 2+ -ISM / pep sensor.
[0008] The second technical object of the present invention is to provide a preparation method of the anti-pollution type electrochemical sensor based on cyclic peptides as described above, which specifically includes the following steps:
[0009] (1) Polish the bare glassy carbon electrode (GC) with alumina powder and thoroughly clean the electrode;
[0010] (2) Place the glassy carbon electrode GC processed in step (1) in 5-6 mL of an aqueous solution containing 2-5 mg of PSS, 8-13 μL of 3,4-ethylenedioxythiophene (EDOT), and 2-3 mg of reduced graphene oxide (rGO), and deposit it at a potential of 1.0 V using the i-t method to obtain the GC / rGO-PEDOT electrode;
[0011] (3) Take 2 mg of calcium ionophore (ETH 5234, N,N-dicyclohexyl-N′,N′-bis(octadecyl)-3-oxapentanediamide), 1 mg of sodium [3,5-bis(trifluoromethyl)phenyl]borate NaTFPB, 66 mg of polyvinyl chloride PVC, and 132 mg of 2-nitrophenyl n-octyl ether o-NPOE, dissolve them in 1.6 mL of tetrahydrofuran THF, and ultrasonically mix to prepare the Ca 2+ selective membrane mixed solution;
[0012] (4) Take the Ca 2+ selective membrane mixed solution and drop it on the already deposited electrode, and dry it overnight to obtain the GC / rGO-PEDOT / Ca 2+ -ISM electrode;
[0013] (5) Dissolve the self-designed polypeptide in ultrapure water to obtain a polypeptide aqueous solution;
[0014] (6) On the Ca 2+Incubate the polypeptide solution on the ion-selective electrode overnight to prepare the anti-fouling electrochemical sensor (GC / rGO-PEDOT / Ca 2+ -ISM / pep) based on cyclic peptide as described above.
[0015] Preferably, in the step (2), the preparation method of the rGO aqueous solution is as follows: First, prepare a 0.5 mg mL -1 aqueous solution of GO, ultrasonicate for 0.5 - 1 h, and introduce N 2 for 15 - 30 minutes; then add 1 mM L-ascorbic acid to the solution, and then adjust the pH to 9 - 10 with ammonia water, and stir vigorously in an oil bath at 85 - 100 °C for 30 - 50 minutes, and cool to room temperature to prepare the rGO aqueous solution.
[0016] Furthermore, the preparation method of the rGO aqueous solution is as follows: First, prepare a 0.5 mg mL -1 aqueous solution of GO, then ultrasonicate for 1 h to uniformly disperse GO in water, and introduce N 2 for 30 minutes to remove O 2 in the solution. Then add 1 mM L-ascorbic acid to the solution, and then adjust the pH to 9 - 10 with ammonia water, and stir vigorously in an oil bath at 90 °C for 40 minutes, and cool to room temperature to prepare the rGO aqueous solution.
[0017] Preferably, in the step (2), the deposition time of the i-t method is 80 s.
[0018] Preferably, in the step (4), 90 μL of the Ca 2+ selective membrane mixed solution is taken.
[0019] Preferably, in the step (6), 10 μL of the polypeptide solution with a concentration of 0.3 mg mL -1 is incubated on the Ca 2+ ion-selective electrode.
[0020] Preferably, the amino acid sequence of the polypeptide is: DOPA-EKSTKESTKESTKEK-DOPA, where 3,4-dihydroxyphenylalanine (DOPA) is modified at both ends of the polypeptide, and the middle part is alternately arranged with hydrophilic amino acids lysine, glutamic acid, and serine.
[0021] The third technical object of the present invention is to provide an application of the anti-fouling electrochemical sensor based on cyclic peptide as described above in monitoring the marine environment.
[0022] Specifically, the anti-fouling electrochemical sensor based on cyclic peptide is used to detect calcium ions in seawater.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1) The present invention develops an all-solid-state calcium ion selective electrochemical sensor based on a cyclic polypeptide as an anti-fouling layer for long-term and accurate monitoring of calcium ions in the ocean.
[0025] 2) The present invention uses a self-designed cyclic peptide as an anti-fouling layer. Due to the extremely strong adhesion ability of DOPA at both ends, the two ends of the polypeptide can be adhered to the electrode surface, enabling the polypeptide to form a stable ring structure. Also, because the peptide chain of the cyclic peptide has abundant carbonyl groups and hydroxyl groups, etc., the cyclic peptide has a high hydrogen bond donor / acceptor ability, thus forming a hydration layer to resist proteins or microorganisms, etc. on the interface to achieve the anti-fouling purpose.
[0026] 3) The method of surface modification with zwitterionic peptides of the present invention significantly reduces bacterial cell adhesion and inhibits the formation of biofilms, attached bacterial cells, and the enclosed bacterial community in extracellular polymeric substances. In addition, the sensor still maintains good selectivity, excellent stability, and a low detection limit after modification with the polypeptide.
[0027] In summary, the present invention develops an anti-fouling all-solid-state calcium ion selective electrochemical sensor, which has broad potential in monitoring the marine environment. Description of the Drawings
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only the embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained according to the provided drawings without creative efforts.
[0029] Figure 1 Morphology and Raman diagram of the GC electrode after depositing rGO-PEDOT.
[0030] Figure 2 For MD simulation experiments, MSD curves, and contact angles.
[0031] Figure 3 For GC / rGO-PEDOT / Ca 2+ -ISM, GC / rGO-PEDOT / Ca 2+ -ISM / pep, GC / Ca 2+ Electrochemical response curves of -ISM.
[0032] Figure 4 Images of the plates after spreading the bacterial solutions rinsed after soaking the negative and positive samples and different electrodes in Escherichia coli and Staphylococcus aureus.
[0033] Figure 5Detection results of the growth of Escherichia coli and Staphylococcus aureus on different modified interfaces.
[0034] Figure 6 Fluorescence detection results of the anti-pollution performance of different interfaces after soaking in Escherichia coli and Staphylococcus aureus solutions respectively.
[0035] Figure 7 Detection results of the reproducibility, stability, selectivity and long-term anti-pollution ability of the anti-pollution calcium ion electrochemical sensor prepared by the present invention. Detailed implementation manners
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0037] The special term "embodiment" used here does not necessarily mean that any embodiment described as "exemplary" is better than or superior to other embodiments. For the performance index tests in the embodiments of the present application, unless otherwise specified, conventional test methods in the art are adopted. It should be understood that the terms described in the present application are only used to describe specific embodiments and are not intended to limit the content disclosed in the present application.
[0038] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as those commonly understood by those of ordinary skill in the art to which the present application belongs; the test methods and technical means not specifically mentioned in the present application are all the experimental methods and technical means commonly adopted by those of ordinary skill in the art.
[0039] To better illustrate the content of the present application, numerous specific details are given in the following specific embodiments. Those skilled in the art should understand that the present application can still be implemented without some specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail to highlight the gist of the present application.
[0040] On the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the obtained technical solutions belong to the content disclosed in the embodiments of the present application.
[0041] The present invention discloses an anti-pollution electrochemical sensor based on cyclic peptides and a preparation method thereof.
[0042] It should be noted that the experimental methods in the following embodiments are all conventional methods unless otherwise specified, and are carried out according to the technologies or conditions described in the literature in this field or according to the product specifications. The materials, reagents, etc. used in the following embodiments can be obtained from commercial channels unless otherwise specified.
[0043] The materials and reagents used in the present invention are as follows:
[0044] The designed peptide (pep, DOPA-EKSTKESTKESTKEK-DOPA, purity > 95%) was synthesized by Hefei Guotai Biotechnology Co., Ltd. 3,4-Ethylenedioxythiophene (C 6 H 6 O 2 S, EDOT), graphene oxide powder (GO, > 99%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Sodium [3,5-bis(trifluoromethyl)phenyl]borate (NaTFPB), polyvinyl chloride (PVC), 2-nitrophenyl n-octyl ether (o-NPOE), and calcium ionophore were purchased from Sigma-Aldrich (Shanghai).
[0045] Ultra-pure water (resistivity ≤ 18 MΩ·cm -1 ) was used throughout the experiment. All chemical substances were of analytical grade and were used without further purification.
[0046] The instruments used in the present invention are as follows:
[0047] All electrochemical measurements were carried out at room temperature using a CHI660E electrochemical workstation. The morphologies of various modified surfaces were characterized using a Hitachi S-4800 scanning electron microscope (SEM) (Hitachi Group, Japan). The binding state of the rGO-PEDOT composite was confirmed by a Raman spectrometer (Horiba scientific-LabRAM HR evolution). A JC2000D1 contact angle measuring instrument (Shanghai Zhongchen Digital Technology Equipment Co., Ltd., China) was used for the water contact angle test of different modified interfaces. Fluorescent observation of bacteria attached to the samples was carried out using a TCS-SP5 laser confocal microscope (Leica, Germany). An eight-channel capacitance-coupled non-contact conductivity detector (manufactured by eDAQ Pty Ltd., Sydney, Australia) was used to online monitor the conductivity changes of the water medium in the test glass tube (OD = 5.0 mm, ID = 4.0 mm).
[0048] To better understand the present invention, the following embodiments are used to further specifically elaborate on the present invention, but it should not be construed as a limitation of the present invention. For some non-essential improvements and adjustments made by those skilled in the art according to the above-mentioned invention content, they are also considered to fall within the protection scope of the present invention.
[0049] Example 1 Preparation of an anti-pollution calcium ion electrochemical sensor (GC / rGO-PEDOT / Ca 2+ -ISM / pep)
[0050] (1) Polish the bare glassy carbon electrode (GC) with alumina powder and thoroughly clean the electrode;
[0051] (2) Place the GC in 5 mL of an aqueous solution containing 5 mg of PSS, 10 μL of 3,4-ethylenedioxythiophene (EDOT), and 2.5 mg of reduced graphene oxide (rGO). Using the i-t method, deposit at a potential of 1.0 V for 80 s to obtain the GC / rGO-PEDOT electrode;
[0052] (3) Dissolve 2 mg of calcium ionophore, 1 mg of NaTFPB, 66 mg of PVC, and 132 mg of o-NPOE in 1.6 mL of THF and ultrasonically mix to prepare the Ca 2+ selective membrane mixed solution;
[0053] (4) Take 90 μL of the Ca 2+ selective membrane mixed solution and drop it on the already deposited electrode, dry overnight to obtain the GC / rGO-PEDOT / Ca 2+ -ISM electrode;
[0054] (5) Dissolve the self-designed polypeptide in ultrapure water to obtain a polypeptide aqueous solution;
[0055] (6) Take 10 μL of a polypeptide with a concentration of 0.3 mg mL -1 and incubate it on the Ca 2+ ion-selective electrode overnight to prepare the anti-pollution Ca 2+ electrochemical sensor (GC / rGO-PEDOT / Ca 2+ -ISM / pep).
[0056] Example 2
[0057] The preparation of the anti-pollution calcium ion electrochemical sensor (GC / rGO-PEDOT / Ca 2+ -ISM / pep) is different from Example 1 in that: Place the GC in 6 mL of an aqueous solution containing 3 mg of PSS, 11 μL of 3,4-ethylenedioxythiophene (EDOT), and 2 mg of reduced graphene oxide (rGO). Using the i-t method, deposit at a potential of 1.0 V for 80 s to obtain the GC / rGO-PEDOT electrode;
[0058] To further prove the beneficial effects of the present invention for better understanding, the following comparative examples and experimental examples further clarify the technical features disclosed by the present invention, but it should not be construed as a limitation to the present invention. Improvements made by those skilled in the art based on the above-mentioned inventive content without creative work are also considered to fall within the protection scope of the present invention.
[0059] Control Example 1 Preparation of GC / rGO-PEDOT / Ca 2+ -ISM electrode
[0060] (1) Polish the bare glassy carbon electrode (GC) with alumina powder and thoroughly clean the electrode;
[0061] (2) Place the GC in 5 mL of an rGO aqueous solution containing 1 mg mL -1 PSS and 0.02 M EDOT, and use the i-t method to deposit at a potential of 1.0 V for 80 s to obtain the GC / rGO-PEDOT electrode;
[0062] (3) Take 2 mg of calcium ionophore, 1 mg of NaTFPB, 66 mg of PVC, and 132 mg of o-NPOE and dissolve them in 1.6 mL of THF, and ultrasonically mix to prepare the Ca 2+ selective membrane mixed solution;
[0063] (4) Take 90 μL of the Ca 2+ selective membrane mixed solution and drop it on the already deposited electrode, and dry it overnight to obtain the GC / rGO-PEDOT / Ca 2+ -ISM electrode.
[0064] Experiment 1: Characterize the morphology and characteristic peaks of the deposited rGO-PEDOT / PSS and PEDOT / PSS by scanning electron microscopy, transmission electron microscopy, and Raman. The results are as Figure 1 shown. Among them, (A) is the scanning electron microscopy image of rGO-PEDOT, (B) is the transmission electron microscopy image of rGO-PEDOT, and (C) is the Raman diagram of rGO-PEDOT / PSS and PEDOT / PSS.
[0065] After depositing rGO-PEDOT / PSS, there are many porous and wrinkled structures on the surface of the glassy carbon electrode, effectively increasing the reaction area and significantly improving the conductivity of the electrode ( Figure 1 A). Further, TEM shows the polymerization of PEDOT / PSS (dark dots) on the surface of rGO sheets ( Figure 1 B). The results reveal the internal structure of rGO-PEDOT / PSS and show that PSS passes through the sp between rGO and PSS 2The π-π interactions between electronic accumulations are attached to the rGO sheets. Structurally, the Raman spectra of PEDOT / PSS and rGO-PEDOT / PSS ( Figure 1 C) show characteristics different from those of pure PEDOT. Their Raman shifts move to higher wavenumbers by 5 - 35 cm - -1 compared to pure PEDOT. Additionally, the superposition of the same functional groups results in the Raman intensity of rGO-PEDOT / PSS being greater than that of PEDOT / PSS. Furthermore, it is also found that both composite materials have vibration peaks at 2949 cm - -1 and 2870 cm - -1, which are attributed to the asymmetric stretching vibration and symmetric stretching vibration of CH 2 , which reflects the carbon chain structure of PSS. In PEDOT / PSS and rGO-PEDOT / PSS, the symmetry is mainly reflected in the symmetric stretching vibration of C α =C β (-O). Their Raman shifts are located at 1430 cm - -1 and 1437 cm - -1 respectively. This result indicates that the interaction between PEDOT / PSS and rGO causes a change in the polarizability, and this change reflects the redistribution of the electron cloud density, resulting in a change in the symmetry structure of the rGO-PEDOT / PSS composite material relative to PEDOT / PSS.
[0066] Experiment 2: Characterization of the polypeptide modification layer
[0067] Molecular dynamics (MD) simulation experiments were carried out using Materials Studio software. The dynamics calculation of dynamics was performed using the forcite calculation section in the analysis dynamics simulation, and all atoms were parameterized using the COMPASSIII force field during the calculation. In the molecular dynamics simulation, 10 polypeptides, 50 Ca 2+ and 3000 water molecules were randomly inserted into the simulation box (20×10×10 nm 3 ). In addition, we also used Materials studio software to analyze the MSD curve in the analysis dynamics. In the Edit set module, Ca 2+ was selected as the analysis ion, and then in the forcite Analysis section of the analysis dynamics, Mean square components was set as the measurement parameter. The MSD curve of Ca 2+ was obtained by analyzing the entire trajectory file of Ca 2+ , as shown in Figure 2 . Among them, (A) is the MD simulation experiment of the initial state of the peptide for Ca2+ and water molecules, (B) shows Ca in the MD simulation experiment of the final state of the peptide 2+ and water molecules, (C) shows Ca at the peptide interface in the simulation 2+ MSD curve, (D) shows the water contact angle of Ca 2+ -ISM and Ca 2+ -ISM / pep.
[0068] From the initial state ( Figure 2 A) to the final state ( Figure 2 B), it can be seen that the designed polypeptide has strong hydrophilicity and can bind a large number of water molecules to form a dense hydration layer. And from Figure 2 B, it can also be seen that Ca 2+ can penetrate through the polypeptide structure, indicating that the presence of the polypeptide does not affect the diffusion of Ca 2+ . Finally, through the analysis of the MSD curve, we obtain Figure 2 C, and then use the Figure 2 C data to calculate the diffusion coefficient to be 0.018 A 2 / ps, which can further prove that the presence of the polypeptide does not affect the diffusion of Ca 2+ . Finally, we measure the water contact angle in air. As Figure 2 shown in D, the contact angle of Ca 2+ -ISM without modified polypeptide is 94.80 ± 0.74, and the contact angle of Ca 2+ -ISM modified with polypeptide (Ca 2+ -ISM / pep) is 12.21 ± 0.97. The decrease in the contact angle indicates that the designed polypeptide sequence has good hydrophilicity, and at the same time proves that the polypeptide is successfully modified onto Ca 2+ -ISM.
[0069] Experiment 3: Influence of surface coating on the potential response of the sensor
[0070] As Figure 3 shown, the electrochemical response curves of GC / rGO-PEDOT / Ca 2+ -ISM, GC / rGO-PEDOT / Ca 2+ -ISM / pep, GC / Ca 2+ -ISM are presented, where (A) shows GC / rGO-PEDOT / Ca 2+ -ISM (a), GC / rGO-PEDOT / Ca 2+ -ISM / pep (b), GC / Ca 2+ -ISM (c) in the concentration range of 1.0×10 -9 ~1.0×10 -1 mol / L CaCl 2EMF response potential time in solution. (B) is GC / rGO-PEDOT / Ca 2+ -ISM (a), GC / rGO-PEDOT / Ca 2+ -ISM / pep (b), GC / Ca 2+ Typical dynamic potential responses of -ISM (c) over time. (C) is GC / rGO-PEDOT / Ca 2+ -ISM (a), GC / rGO-PEDOT / Ca 2+ -ISM / pep (b), GC / Ca 2+ Calibration curves of -ISM (c). (D) At 1.0×10 -3 mol / L CaCl 2 Solution, the measured GC / rGO-PEDOT / Ca 2+ -ISM (a), GC / rGO-PEDOT / Ca 2+ -ISM / pep (b) and GC / Ca 2+ Chronopotentiograms of -ISM (c).
[0071] The GC / rGO-PEDOT / Ca 2+ -ISM, GC / rGO-PEDOT / Ca 2+ -ISM / pep, GC / rGO-PEDOT / Ca 2+ -ISM / pep, GC / Ca 2+ -ISM was successively measured for its electromotive force in 10 -1 mol / L to 10 -9 mol / L CaCl 2 Solution, and their electrode potential response curves were obtained respectively, as shown in Figure 3 Figure A.
[0072] Figure 3 Figure B shows the response time required for the electrode to reach a stable potential. The electrodes GC / rGO-PEDOT / Ca 2+ -ISM, GC / rGO-PEDOT / Ca 2+ -ISM / pep both reached stability within 5 s. From the previous calculations, it can be seen that the polypeptide does not affect the diffusion rate of calcium ions, and modifying the polypeptide does not affect the response time of the electrode. While the GC / Ca 2+ -ISM electrode without deposited rGO-PEDOT took approximately 30 s to reach a stable potential, required a longer response time, and exhibited potential drift. This may be due to the porous wrinkled structure of rGO-PEDOT / PSS, which effectively increased the reaction area and improved the electron conduction ability.
[0073] It can be seen from Figure 3 C that without rGO-PEDOT as the solid conduction layer GC / Ca 2+ -ISM electrode, the linear range is 10 - 1 mol / L to 10 -5 mol / L, and the detection limit is 10 -5.09 . For the GC / rGO-PEDOT / Ca 2+ -ISM electrode deposited with rGO-PEDOT / PSS, the linear range is 10 -1 mol / L to 10 -9 mol / L, and the detection limit is 10 -7.18 . For the GC / rGO-PEDOT / Ca 2+ -ISM / pep electrode modified with polypeptide, the detection limit in the same linear range is 10 -7.16 . Both the GC / rGO-PEDOT / Ca 2+ -ISM / pep and GC / rGO-PEDOT / Ca 2+ -ISM have a wide detection range and a low detection limit, and the detection performance of the electrode is not reduced after modifying with polypeptide. Finally, the chronopotentiometry was used to characterize the short-term potential stability of the Ca 2+ -ISM electrode. It can be seen from Figure 3 D that for the GC / rGO-PEDOT / Ca 2+ -ISM electrode deposited with rGO-PEDOT, the potential drift (28.33 μV s -1 ) and that of the GC / rGO-PEDOT / Ca 2+ -ISM / pep (31.67 μV s -1 ) are much smaller than that of the GC / Ca 2+ -ISM (0.82 mV s -1 ). It can be obtained from Figure 3 D and according to the formula △E / △t = I / C that the low-frequency capacitance of the GC / rGO-PEDOT / Ca 2+ -ISM electrode is about 35.30 μF, which is significantly higher than that of the GC / Ca 2+ -ISM (1.22 μF). Both the GC / rGO-PEDOT / Ca 2+ -ISM / pep and GC / rGO-PEDOT / Ca 2+ -ISM have good potential stability.
[0074] Experiment 4: Use the plate counting method to evaluate the anti-pollution ability of the proposed anti-pollution Ca 2+ electrode pair against bacteria
[0075] The anti-pollution performance of the anti-fouling Ca 2+ selective electrode was evaluated using Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli). The unmodified Ca 2+ selective membrane after cleaning and the Ca 2+ selective membrane incubated with polypeptide were respectively immersed in bacterial suspensions of Escherichia coli and Staphylococcus aureus with a concentration of 10 6 CFU mL -1 at room temperature for 24 h, and the bacteria adhering to the electrode surface were rinsed off with 1 mL of PBS solution. Then, the rinsed bacterial suspension was diluted 100 times, and 10 μL of the diluted bacterial suspension was evenly spread on a Luria-Bertani (LB) broth agar growth plate. After incubating overnight at 37 °C, the viable bacterial colonies on the LB plate were counted. The colony numbers of different modified interfaces were compared.
[0076] Figure 4 is the comparison chart of Ca 2+ -ISM / pep and Ca 2+ -ISM. From left to right are 10 6 CFU mL -1 colony counts (positive control), colony counts of Ca 2+ -ISM washing solution, colony numbers of Ca 2+ -ISM / pep rinsing solution and the image of a blank LB broth agar growth plate (negative control). The first layer is Escherichia coli, and the second layer is Staphylococcus aureus. It can be seen from Figure 4 that both in Escherichia coli and Staphylococcus aureus, Ca 2+ -ISM / pep is significantly less than Ca 2+ -ISM, indicating that the designed polypeptide has excellent anti-pollution ability.
[0077] Experiment 5: Comparing the bacterial growth curves of different modified interfaces to characterize the anti-pollution ability of different interfaces
[0078] The anti-pollution performance of the prepared different modified interfaces was evaluated using Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria).
[0079] First, the growth curves of Escherichia coli and Staphylococcus aureus were determined by real-time online monitoring of the conductivity change of LB broth using a multi-channel non-contact conductivity sensor (CCS).
[0080] First, the unmodified calcium ion selective membrane and the calcium ion selective membrane incubated with polypeptide after cleaning were respectively immersed in bacterial suspensions of Escherichia coli and Staphylococcus aureus with a concentration of 10 6 CFU mL -1In the bacterial suspensions of Escherichia coli and Staphylococcus aureus for 24 h, then select and place them in test tubes (5 mm NMR tube, NORELL, USA) containing LB broth. After that, add 10 6 CFU / mL -1 of the bacterial suspensions of Escherichia coli and Staphylococcus aureus as positive controls, and LB broth as a negative control, and then insert them into the CCS in sequence.
[0081] As Figure 5 is the bacterial growth curves of Escherichia coli and Staphylococcus aureus under different conditions. (A) is the growth curve of Escherichia coli; (B) is the growth curve of Staphylococcus aureus. The horizontal axis represents the incubation time, and the vertical axis represents the normalized apparent conductivity value (NACV, expressed in voltage). In the stationary phase, the NACV value of the Ca 2+ -ISM / pep curve is significantly higher than that of Ca 2+ -ISM. This is because the presence of the polypeptide forms a hydrated layer on the Ca 2+ -ISM interface, effectively reducing bacterial adhesion and the number of bacteria at the interface, thereby enhancing the anti-pollution ability of Ca 2+ -ISM / pep.
[0082] Experiment 6: Observation of bacterial and protein adhesion at the interface by laser confocal microscopy
[0083] Expose the unmodified Ca 2+ selective membrane and the Ca 2+ selective membrane incubated with the polypeptide to the bacterial suspensions of Escherichia coli and Staphylococcus aureus at 10 6 CFU / mL -1 for 24 h. Stain the bacterial cells attached to the Ca 2+ selective membrane with 3.34 μM SYTO 9 (live bacteria) and 20 μM PI (dead bacteria) for 30 minutes at room temperature in the dark. Then observe the stained bacteria by confocal laser scanning microscopy. Since bacteria adhering to the membrane surface secrete extracellular polymeric substances (EPS), the proteins on the membrane surface are stained with ConA fluorescent dye for 30 minutes, and the stained proteins are observed by confocal laser scanning microscopy.
[0084] Figure 6 are the fluorescence detection results of the anti-pollution performance of different interfaces after soaking in the Escherichia coli and Staphylococcus aureus solutions respectively. Among them, Figure 6 are the confocal laser scanning microscopy images of the biofilms on Ca 2+ -ISM and Ca 2+ -ISM / pep respectively. The biofilms are stained with SYTO9 (green) and Con A (blue) for live cells and EPS respectively.
[0085] As Figure 6 shown, a large number of bacteria and EPS adhered to Ca 2+ -ISM after 24 h, which indicates that Ca 2+ -ISM will have the problem of biofouling during long-term testing. While Ca 2+ -ISM / pep only adhered very few bacteria and EPS, and the quantity was much less than that of unmodified Ca 2+ -ISM. These results all confirmed that Ca 2+ -ISM / pep has excellent anti-pollution ability.
[0086] Experiment 7: This example verifies the detection results of the reproducibility, stability, selectivity and long-term anti-pollution ability of the prepared anti-pollution type Ca 2+ electrochemical sensor
[0087] Using chronopotentiometry, the reproducibility and stability of the GC / rGO-PEDOT / Ca 2+ -ISM / pep electrode were evaluated.
[0088] To explore the long-term anti-pollution ability of the proposed anti-pollution type Ca 2+ electrochemical sensor, a series of potential measurements were carried out after the electrode was in contact with seawater at different stages, and the change of the Nernst response slope before and after soaking was observed.
[0089] To test the selectivity of the proposed anti-pollution type Ca 2+ electrochemical sensor, the differential solution method was used, and the main metal ions in seawater were selected as interfering ions for testing.
[0090] As Figure 7 , (A) is the repeatability of the chronopotentiogram of GC / rGO-PEDOT / Ca 2+ -ISM / pep. (B) is the reproducibility of the chronopotentiogram of GC / rGO-PEDOT / Ca 2+ -ISM / pep. (C) is the change of the Nernst response slope after the electrode was soaked in seawater for 60 days. (D) is the selectivity coefficient of GC / rGO-PEDOT / Ca 2+ -ISM / pep.
[0091] As Figure 7 A shows that the same electrode of GC / rGO-PEDOT / Ca 2+ -ISM / pep has good repeatability. Figure 7 The result of B shows that different GC / rGO-PEDOT / Ca 2+-ISM / pep electrodes have good reproducibility. Therefore, experiments show that rGO-PEDOT with a large capacitance, as the Ca 2+ The solid contact ion-electron charge transfer conduction layer between the selective membrane and the glassy carbon matrix can effectively improve the potential stability and enhance the ability of rapid charge transfer.
[0092] As Figure 7 shown in C, before immersion, the Nernst response slope of the GC / rGO-PEDOT / Ca 2+ -ISM / pep electrode was 30.38 mV / dec, and after 50 days of immersion, the Nernst response slope remained stable at 28.87 mV / dec. For the GC / rGO-PEDOT / Ca 2+ -ISM electrode, the Nernst slope could only remain stable within 15 days of immersion in seawater (stable from 29.81 mV / dec to 25.11 mV / dec), while after 50 days, the Nernst slope decreased significantly to 17.53 mV / dec. This shows that GC / rGO-PEDOT / Ca 2+ -ISM / pep has good long-term stability in seawater due to its excellent anti-pollution ability. GC / rGO-PEDOT / Ca 2+ -ISM / pep has good selectivity. The separation solution method was used to evaluate the selectivity of the prepared electrodes, and Co 2+ , Pb 2+ , Zn 2+ , Mg 2+ , Cu 2+ , Ni 2+ , Na + , K + were selected as interfering ions. As Figure 7 shown in D, GC / rGO-PEDOT / Ca 2+ -ISM / pep has good selectivity.
[0093] Experiment 8: Testing of actual samples
[0094] Taking GC / rGO-PEDOT / Ca 2+ -ISM / pep as the research object, the content of Ca 2+ in seawater samples was detected and analyzed by the standard curve method. Taking seawater samples as the research object, a comparative analysis was carried out with the experimental results of inductively coupled plasma atomic emission spectrometry, a traditional detection method.
[0095] The specific experimental results are shown in Table 1 below. It can be seen that the GC / rGO-PEDOT / Ca 2+ -ISM / pep electrode for Ca 2+The experimental determination results of the content are basically consistent with the test results of inductively coupled plasma atomic emission spectrometry.
[0096] Table 1
[0097]
[0098] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A cyclic peptide-based anti-pollution electrochemical sensor, characterized in that: The electrochemical sensor is a GC / rGO-PEDOT / Ca2+ electrochemical sensor with a glassy carbon electrode as a substrate, reduced graphene oxide and 3,4-ethylenedioxythiophene as a solid conductive layer, a calcium ion selective membrane as a detection layer, and a self-designed polypeptide as an antifouling layer. 2+ -ISM / pep sensors; The preparation method of the electrochemical sensor comprises the following steps: (1) Polish the bare glassy carbon electrode (GC) with alumina powder and clean the electrode thoroughly; (2) placing the glassy carbon electrode GC treated in step (1) in 5-6 mL of an aqueous solution containing PSS, 3,4-ethylenedioxythiophene (EDOT) and graphene oxide (rGO), and depositing for 80 s at a potential of 1.0 V using the it method to obtain a GC / rGO-PEDOT electrode; (3) Calcium ion carrier, sodium [3,5-bis(trifluoromethyl)phenyl]borate, polyvinyl chloride, and 2-nitrophenyl n-octyl ether were dissolved in tetrahydrofuran and ultrasonically mixed to prepare Ca 2+ Selective membrane mixed solution; (4) Take 90 μL Ca 2+ The selective membrane mixed solution was dropped on the deposited electrode and dried overnight to obtain GC / rGO-PEDOT / Ca 2+ -ISM electrode; (5) dissolving the independently designed polypeptide in ultrapure water to obtain a polypeptide aqueous solution; (6) In Ca 2+ The peptide solution was incubated on the ion selective electrode overnight to prepare the anti-fouling electrochemical sensor based on cyclic peptide (GC / rGO-PEDOT / Ca 2+ -ISM / pep); In step (2), the preparation method of the rGO aqueous solution is: first prepare 0.5 mg mL -1 The GO aqueous solution was ultrasonicated for 0.5-1h and N2 was introduced for 15-30 minutes; then 1mM L-ascorbic acid was added to the solution, and then the pH was adjusted to 9-10 with ammonia water, and the solution was vigorously stirred in an oil bath at 85-100°C for 30-50 minutes and cooled to room temperature to prepare the rGO aqueous solution; In step (6), 10 μL of the solution was taken to obtain a concentration of 0.3 mg / mL -1 The peptide solution was incubated in Ca 2+ On ion selective electrodes; The amino acid sequence of the polypeptide is: DOPA-EKSTKESTKESTKEK-DOPA.
2. The anti-pollution electrochemical sensor based on cyclic peptide according to claim 1, characterized in that: In step (2), the ratio of PSS, 3,4-ethylenedioxythiophene (EDOT), and graphene oxide (rGO) is 2-5 mg: 8-13 μL: 2-3 mg.
3. The anti-pollution electrochemical sensor based on cyclic peptide according to claim 1, characterized in that: In step (3), the ratio of the amount of calcium ion carrier, sodium [3,5-bis(trifluoromethyl)phenyl]borate, polyvinyl chloride, 2-nitrophenyl n-octyl ether and tetrahydrofuran is 2 mg: 1 mg: 66 mg: 132 mg: 1.6 mL.
4. Use of the anti-pollution electrochemical sensor based on cyclic peptide as claimed in claim 1 in monitoring marine environment.
5. The use according to claim 4, characterized in that: The anti-pollution electrochemical sensor based on cyclic peptide is used for detecting calcium ions in seawater.
Citation Information
Patent Citations
Biosensor as well as preparation method, application and application method thereof
CN113252745A
Y-type polypeptide modified ion selective electrode as well as preparation method and application thereof
CN117849144A
Electrochemical sensor for simultaneous detection of dopamine and serotonin and manufacturing method thereof
US20230400430A1